Accurate numerical simulation of the far-field tsunami caused by the 2011 Tohoku earthquake, including the effects of Boussinesq dispersion, seawater density stratification, elastic loading, and gravitational potential change - Baba, Toshitaka; Allgeyer, Sébastien; Hossen, Md. Jakir; Cummins, Phil R.; Tsushima, Hiroaki; Imai, Kentaro; Yamashita, Kei; Kato, Toshihiro (© 2017 Elsevier Ltd, 2018)
This article was published in the Journal of Ocean Modelling [© 2017 Elsevier Ltd] and the definite version is available at : http://doi.org/10.1016/j.ocemod.2017.01.002 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S1463500317300082?via%3Dihub